The system of giving employee compensation at PT Tasti Anugrah Mandiri - Muhammad Asir; Reni Fatmasari Syafruddin (PINISI Discretion Review, 2021)
Companies must give more attention to employees so that employees can think actively and work optimally. One of the factors that influence the emergence of commitment to employees is the provision of fair compensation. This study aims to determine the employee compensation system and the factors that influence employee compensation at PT Tasti Anugrah Mandiri. The type of research used is descriptive qualitative, namely the author describes the results of observations and direct interviews with the marketing (Salesman). This research was conducted from September to October 2020. The results of the study indicate that the compensation system at PT Tasti Anugrah Mandiri uses a work performance system or target achievement where this system prioritizes achieving targets made by employees in selling company products. The factors that form the basis for providing compensation are the company's ability and willingness and employee productivity.